MICS/ISM Meander-Line Microstrip Antenna Encapsulated in Oblong-Shaped Pod for Gastrointestinal Tract Diagnosis - Supakit Kawdungta; Akkarat Boonpoonga; Chuwong Phongcharoenpanich (My University, 2021)
In light of the growth in demand for multiband antennas for medical applications, this research proposes a MICS/ISM meander-line microstrip antenna encapsulated in an oblong-shaped pod for use in diagnoses of the gastrointestinal tract. The proposed antenna is operable in the Medical Implant Communication System (MICS) and the Industrial, Scientific and Medical (ISM) bands. The antenna structure consists of a meander-line radiating patch, a flipped-L defected ground plane, and a loading resistor for antenna miniaturization. The MICS/ISM microstrip antenna encapsulated in an oblong-shaped pod was simulated in various lossy-material environments. In addition, the specific absorption rate (SAR) was calculated and compared against the IEEE C95.1 standard. For verification, an antenna prototype was fabricated and experiments carried out in equivalent liquid mixtures, the dielectric constants of which resembled human tissue. The measured impedance bandwidths (|S11| ≤ −10 dB) for the MICS and ISM bands were 398–407 MHz and 2.41–2.48 GHz. The measured antenna gains were −38 dBi and −13 dBi, with a quasi-omnidirectional radiation pattern. The measured SAR was substantially below the maximum safety limits. As a result, the described MICS/ISM microstrip antenna encapsulated in an oblong-shaped pod can be used for real-time gastrointestinal tract diagnosis. The novelty of this work lies in the use of a meander-line microstrip, flipped-L defected ground plane, and loading resistor to miniaturize the antenna and realize the MICS and ISM bands.
Keywords: Patch antenna; Ground plane; ISM band; Wireless Body Area Networks